Philosophy and Greek Philosophy on Marriage Dispensation: Normativity and Historicity - Dimyati, Yayat; Latifah, Hanik (Sekolah Tinggi Agama Islam At-Tahdzib Jombang, 2025)
The study examines the relationship between Islamic and Greek philosophy to understand the concept of marriage dispensation, with an interdisciplinary approach that emphasizes two main aspects: normativity and historicity. Marriage dispensation is understood as a form of legal exception that allows marriage below the ideal age based on considerations of welfare. Marriage dispensation is not just a legal policy, but a reflection of the meeting between rationality, ethics, and responses to social reality. Greek philosophy, especially in the thoughts of Plato and Aristotle, views marriage as part of a social structure that plays an important role in achieving moral virtue and social order. Marriage is based on the principles of natural law and teleology. Everything is directed to achieve noble and rational goals. Marriage in Islamic philosophy, especially according to Al-Farabi, Ibn Sina, and Al-Ghazali, adopts many aspects of Greek philosophy, but by integrating elements of revelation, spiritual values, and the framework of sharia into thought. One of the main pillars in Islamic legal philosophy that is the meeting point between rationality and religious norms is maqāṣid al-syarīʿah, namely the theory of the objectives of Islamic law which include protection of religion, soul, mind, descendants, and property. Marriage dispensation can be seen as an effort to fulfill the objectives of Islamic law when ideal conditions are not met. Through a historical approach, this study traces the path of intellectual transmission from Greece to the Islamic world and how philosophical thought was transformed in the context of Islamic law. While normatively, this study shows that Islamic philosophy does not only passively inherit Greek ideas, but actively adapts them to divine values. The results of this study confirm that the philosophical approach to marriage dispensation has great potential in strengthening Islamic legal reform to be more adaptive, rational, and ethical amidst contemporary social dynamics.